Induction and recovery of CpG site specific methylation changes in human bronchial cells after long-term exposure to carbon nanotubes and asbestos. (April 2020) - Öner, Deniz; Ghosh, Manosij; Coorens, Robin; Bové, Hannelore; Moisse, Matthieu; Lambrechts, Diether; Ameloot, Marcel; Godderis, Lode; Hoet, Peter H.M.
Highlights: At non-cytotoxic doses, CNTs are incorporated with in the nucleus after a four weeks period. Exposure to MWCNTs induced a single hypomethylation at a CpG site and gene promoter region. SWCNTs/amosite induced hypermethylation at CpG sites after sub-chronic exposure. SWCNT/amosite induced changes in 'transcription factor activity' and 'sequence-specific DNA binding' After the recovery period, hypermethylation and hypomethylation were noted for both SWCNTs and amosite. Abstract: Introduction: Inhalation of asbestos induces lung cancer via different cellular mechanisms. Together with the increased production of carbon nanotubes (CNTs) grows the concern about adverse effects on the lungs given the similarities with asbestos. While it has been established that CNT and asbestos induce epigenetic alterations, it is currently not known whether alterations at epigenetic level remain stable after withdrawal of the exposure. Identification of DNA methylation changes after a low dose of CNT and asbestos exposure and recovery can be useful to determine the fibre/particle toxicity and adverse outcome. Methods: Human bronchial epithelial cells (16HBE) were treated with a low and non-cytotoxic dose (0.25 µg/ml) of multi-walled carbon nanotubes (MWCNTs-NM400) or single-walled carbon nanotubes (SWCNTs-SRM2483) and 0.05 µg/ml amosite (brown) asbestos for the course of four weeks (sub-chronic exposure). After this treatment, the cells were further incubated (without particle/fibre) for two weeks, allowing recovery from the exposure (recovery period). Nuclear depositions of the CNTs were assessed using femtosecond pulsed laser microscopy in a label-free manner. DNA methylation alterations were analysed using microarrays that assess more than 850 thousand CpG sites in the whole genome. Results: At non-cytotoxic doses, CNTs were noted to be incorporated with in the nucleus after a four weeks period. Exposure to MWCNTs induced a single hypomethylation at a CpG site and gene promoter region. No change in DNA methylation was observed after the recovery period for MWCNTs. Exposure to SWCNTs or amosite induced hypermethylation at CpG sites after sub-chronic exposure which may involve in 'transcription factor activity' and 'sequence-specific DNA binding' gene ontologies. After the recovery period, hypermethylation and hypomethylation were noted for both SWCNTs and amosite. Hippocalcinlike 1 ( HPCAL1), protease serine 3 ( PRSS3), kallikrein-related peptidase 3 (KLK3), kruppel like factor 3 ( KLF3) genes were hypermethylated at different time points in either SWCNT-exposed or amosite-exposed cells. Conclusion: These results suggest that the specific SWCNT (SRM2483) and amosite fibres studied induce hypo- or hypermethylation on CpG sites in DNA after very low-dose exposure and recovery period. This effect was not seen for the studied MWCNT (NM400).